2022
DOI: 10.1038/s41419-022-05429-w
|View full text |Cite
|
Sign up to set email alerts
|

BTN3A1 promotes tumor progression and radiation resistance in esophageal squamous cell carcinoma by regulating ULK1-mediated autophagy

Abstract: Radiotherapy is one of the most effective treatments for esophageal squamous cell carcinoma (ESCC); however, radioresistance is a clinical problem that must urgently be solved. Here, we found that butyrophilin subfamily 3 member A1 (BTN3A1) is upregulated in ESCC tumor tissues compared with nontumor tissues. We also evaluated BTN3A1 expression in patients with ESCC receiving adjuvant radiotherapy. The results demonstrated that BTN3A1 upregulation predicts a poor prognosis for ESCC patients. BTN3A1 overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The analysis of BTN3A1’s prognostic significance revealed an association between elevated BTN3A1 expression and poorer prognosis in glioma patients. Elevated BTN3A1 expression has also been linked to unfavorable outcomes in esophageal squamous cell carcinoma (ESCC), metastatic gastrointestinal stromal tumors (mGISTs), and ovarian cancer (OC) ( 27 , 32 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of BTN3A1’s prognostic significance revealed an association between elevated BTN3A1 expression and poorer prognosis in glioma patients. Elevated BTN3A1 expression has also been linked to unfavorable outcomes in esophageal squamous cell carcinoma (ESCC), metastatic gastrointestinal stromal tumors (mGISTs), and ovarian cancer (OC) ( 27 , 32 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the correlation of BTN3A expression with immune evasion strategies of pancreatic tumor (PC) cells reinforces the role of BTN3A in facilitating tumor progression ( 31 ). A notable recent study elucidated that BTN3A1 overexpression in esophageal squamous cell carcinoma (ESCC) augments radioresistance by modulating the expression and phosphorylation of UNC-51-like autophagy-activating kinase (ULK1), subsequently correlating with adverse prognoses ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto et al indicated that autophagy promotes immune evasion of pancreatic cancer by degrading MHC-I 26 . Yang et al reported that BTN3A1 promotes tumor progression and radiation resistance in esophageal squamous cell carcinoma by regulating ULK1-mediated autophagy 27 . Wang et al also found that PLK1 inhibition enhances the radiosensitivity of breast cancer cells in a manner associated with the suppression of radiation-induced autophagy 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, what is striking is their differential expression in steady-state epithelial tissues versus their respective neoplastic counterparts. This is most evident in BTN3A isoforms which are often upregulated in cancers relative to normal tissue counterparts [ 118 , 120 123 ] (Fig. 1 ).…”
Section: Clinical Translation: Challenges and Opportunitiesmentioning
confidence: 99%